1, 5‐Di(nitramino)tetrazole: High Sensitivity and Superior Explosive Performance1. Issue 35 (19th June 2015) - Fischer, Dennis; Klapötke, Thomas M.; Stierstorfer, Jörg
Abstract Highly energetic 1, 5‐di(nitramino)tetrazole and its salts were synthesized. The neutral compound is very sensitive and one of the most powerful non‐nuclear explosives to date. Selected nitrogen‐rich and metal salts were prepared. The potassium salt can be used as a sensitizer in place of tetracene. The obtained compounds were characterized by low‐temperature X‐ray diffraction, IR and Raman spectroscopy, multinuclear NMR spectroscopy, elemental analysis, and DSC. Calculated energetic performances using the EXPLO5 code based on calculated (CBS‐4M) heats of formation and X‐ray densities support the high energetic performances of the 1, 5‐dinitraminotetrazolates as energetic materials. The sensitivities towards impact, friction, and electrostatic discharge were also explored.